The reading processes of a Scottish Ottomanist: E. J. W. Gibb and his young Ottoman sources. Issue 2 (2nd September 2018) - Gür, Nagihan
ABSTRACT: I shed light on the writing processes of the Ottoman literary narrative that the Scottish Ottomanist Elias John Wilkinson Gibb (1857–1901) created from 1882 until his early death in 1901. I discuss the Young Ottoman reformist Namık Kemal's (1840–1888) influence on Gibb and the extent to which Namık Kemal's criticism of Ottoman poetry is reflected in Gibb's work. Gibb was familiar with Namık Kemal's works through various channels and was profoundly affected by his views and criticism of Ottoman literature. Through some of the primary sources found in the Gibb Collection and the E. G. Browne Papers at the Cambridge University Library, I reveal the writing processes of the literary narrative that Gibb put forward in "Ottoman Literature, " Ottoman Poems, and A History of Ottoman Poetry . Furthermore, I elucidate Gibb's understanding of Ottoman poetry by analyzing his marginalia, translations, and his personal communications. Based on my research, I argue that Gibb's critical attitude was shaped by the literary culture nurtured by Young Ottoman intellectuals as well as their criticism of classical Ottoman literature.